2014
DOI: 10.3892/ol.2014.2358
|View full text |Cite
|
Sign up to set email alerts
|

GSTM3 reverses the resistance of hepatoma cells to radiation by regulating the expression of cell cycle/apoptosis-related molecules

Abstract: Radiotherapy (RT) is a major modality of hepatoma treatment. However, liver tumors often acquire radioresistance, which contributes to RT failure. The exact mechanisms of the radioresistance in hepatoma cells are largely unknown. Glutathione S-transferase M3 (GSTM3) is a phase II transferase, however, recent studies have suggested that GSTM3 is a potential tumor suppressor. The purpose of the present study was to investigate the role of GSTM3 in reversing radioresistance, and to explore the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Following myocardial ischemia/reperfusion injury, enhanced apoptosis has been demonstrated [26]. Studies have indicated that upregulation of p27 significantly enhances cell apoptosis [27].In previous studies, regulation of p27 has been reported at different levels [10]. Alterations of cell cycle regulatory molecules play key roles in various diseases, such as cancer and cardiac injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Following myocardial ischemia/reperfusion injury, enhanced apoptosis has been demonstrated [26]. Studies have indicated that upregulation of p27 significantly enhances cell apoptosis [27].In previous studies, regulation of p27 has been reported at different levels [10]. Alterations of cell cycle regulatory molecules play key roles in various diseases, such as cancer and cardiac injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these eGenes, GSTM3 and HSPA6, are associated with diseases such as HBV for GSTM3 and HCC for both eGenes. [28][29][30][31] These are diseases that disproportionately affect African Americans. 32,33 GSTM3 has also been associated to oxidative stress and specifically several studies have found that epigenetic suppression of GSTM3 in HBV-infected cells causes oxidative stress 29,30 , which can lead to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] These are diseases that disproportionately affect African Americans. 32,33 GSTM3 has also been associated to oxidative stress and specifically several studies have found that epigenetic suppression of GSTM3 in HBV-infected cells causes oxidative stress 29,30 , which can lead to HCC. 28 Furthermore, other studies showed that GSTM3 expression was lowered with promoter hypermethylation 34 and in chemical-induced HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alpha-class Gsts have been reported to play an important role as antioxidant enzymes modulating stress-induced apoptosis pathways (Yang et al , 2001) and are associated with “immunity and defense” (Yun et al , 2009). Gstm3 regulates apoptosis- and proliferation-related pathways and was identified as a tumor suppressor (Sun et al , 2014), whereas theta-class Gsts (Gstt2 and 3) are critical in the early response induced by toxicants, such as D-galactosamine and 1-menaphthyl sulphate, due to altered oxidative stress (Coggan et al , 2002; Yun et al , 2010). Therefore, mice on the restricted diet, atherogenic diet, and lab chow might be more resistant to carcinogens and by-products of oxidative stress, compared to mice on the AIN-93M purified diet.…”
Section: Discussionmentioning
confidence: 99%